2017
DOI: 10.1080/09273948.2017.1391954
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Uveitis at Two University-Based Referral Centres in Cape Town, South Africa

Abstract: This study emphasizes the importance of HIV testing and investigations for infectious causes of uveitis, especially syphilis, in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…2 This resurgence in syphilis cases in the United States corresponds with recent reports of ocular syphilis in nearly all regions of the globe, including the United Kingdom, Australia, South Africa, France, and China. 1,[3][4][5][6][7][8] Ocular syphilis classically presents as uveitis in secondary or tertiary syphilis and has been shown to affect all structures of the eye. 9 Although the timing of syphilis progression varies, a recent study has recorded a median time to ocular symptom development of 11 months following infection.…”
Section: Introductionmentioning
confidence: 99%
“…2 This resurgence in syphilis cases in the United States corresponds with recent reports of ocular syphilis in nearly all regions of the globe, including the United Kingdom, Australia, South Africa, France, and China. 1,[3][4][5][6][7][8] Ocular syphilis classically presents as uveitis in secondary or tertiary syphilis and has been shown to affect all structures of the eye. 9 Although the timing of syphilis progression varies, a recent study has recorded a median time to ocular symptom development of 11 months following infection.…”
Section: Introductionmentioning
confidence: 99%
“…Italy (19.7% of panuveitis; 4.1% of all uveitis) [16] and Australia (5.5% of all uveitis) [17] have also reported higher rates of VKH. A referral centre in South Africa has published on local uveitis patterns with zero reported VKH cases over a 1.5-year period (198 patients) [18].…”
Section: Epidemiologymentioning
confidence: 99%
“…The risk factors most frequently documented are male sex, homosexuality and intravenous drug abuse, but the infection rates are also increasing in females and heterosexual individuals (1)(2)(3)(4)(5)(6)(7)(8). In 3 studies from South Africa, syphilis was identified as the cause of uveitis in 7% to 16.2% of cases (9)(10)(11).Ocular syphilis is diagnosed when ocular inflammation occurs in conjunction with a serologically confirmed systemic syphilis infection, and other causes for inflammation have been excluded. The relationship between ocular syphilis and neurosyphilis has been much debated, but it is assumed that, due to the embryological origin of the retina from the central nervous system, ocular syphilis is a clinical feature of neurosyphilis.…”
Section: Introductionmentioning
confidence: 99%